Temporal accumulation and localization of isoflurane in the C57BL/6 mouse and assessment of its potential contamination in (19)F MRI with perfluoro‐crown‐ether‐labeled cardiac progenitor cells at 9.4 Tesla - Constantinides, Christakis (J Magn Reson Imaging, 2016)
PURPOSE: To assess the uptake, accumulation, temporal stability, and spatial localization of isoflurane (ISO) in the C57BL/6 mouse, and to identify its potential interference with the detection of labeled cardiac progenitor cells using (19)F MRI/MR spectroscopy (MRS). MATERIALS AND METHODS: Objectives are demonstrated using (a) in vitro ISO tests, (b) in vivo temporal accumulation/spatial localization C57BL/6 studies (n = 3), and (c) through injections of perfluoro‐crown‐ether (PFCE) labeled cardiac progenitor cells into femoral muscle areas of the murine hindlimb post‐mortem (n = 1) using (1)H/(19)F MRI/MRS at 9.4 Tesla. Data were acquired using double‐gated spoiled gradient echo images and pulse‐acquire spectra. For the in vivo study, the temporal stability of ISO resonances was quantified using coefficient of variability (CV) (5 min) estimates. RESULTS: Two ISO resonances were observed in vivo that correspond to the ‐CF(3) and ‐OCHF(2) moieties. CV values ranged between 3.2 and 6.4% (‐CF(3)) and 6.4 and 11.2% (‐OCHF(2)). Reductions of the ISO dose (2.0 to 1.7%) at 80 min postinduction had insignificant effects on ISO signals (P = 0.23; P = 0.71). PFCE‐labeled cells exhibited a resonance at −16.25 ppm in vitro that did not overlap with the ISO resonances, a finding that is confirmed with MRS post‐mortem using injected, labeled cells. Based on (19)F MRI, similar in vivo/post‐mortem ISO compartmentalization was also confirmed in peripheral and thoracic skeletal muscles. CONCLUSION: Significant ISO accumulation was observed by (19)F MRS in vivo with temporally stable signals over 90 min postinduction. ISO effects on PFCE labels are anticipated to be minimal but may be more prominent for perfluoropolyether or perfluorooctyl bromide labels. Level of Evidence: 1 Technical Efficacy: Stage 1 J. MAGN. RESON. IMAGING 2017;45:1659–1667